Decreasing urgent repeat cesarean sections by offering complimentary ultrasounds and consultation in rural Burundi: The zigama mama project - Eric McLaughlin; Matthew Nagy; Jean-Bosco Magorwa; Gilbert Kibinakanwa; Rachel McLaughlin (Frontiers Media S.A., 2023)
ObjectiveRepeat urgent cesarean sections (CS) carry an increased risk of severe maternal outcomes. As CS increase in sub-Saharan Africa, creative strategies are necessary to reduce the rate of urgent repeat CS. The Zigama-Mama Project in rural Burundi uses complimentary ultrasounds to create a clinical touchpoint to counsel women with a prior CS for a hospital-based delivery.MethodsFrom July 2019 to June 2020, complimentary ultrasounds were offered to all antenatal patients with prior CS, along with counseling for monitored trial of labor after cesarean (TOLAC) or scheduled repeat CS. Community engagement and feedback from district health centers were evaluated.ResultsIn total, 500 women with a prior CS presented for a complimentary ultrasound. During the intervention year, a relative and absolute reduction in urgent repeat CS (baseline: n = 114 {70.8%}, intervention: n = 97{49.7%}, p < 0.001) was observed, with no significant change in maternal mortality or ruptured uteri. All health center personnel agreed the project improved their confidence in referring women with prior CS.ConclusionOffering complimentary ultrasounds as a clinical touchpoint for scheduling a monitored delivery or CS for women at high risk for delivery complication may be an affordable and creative strategy to care for women with previous CS during subsequent deliveries.